DESARROLLO URBANO SOSTENIBLE: UNA APROXIMACION TEORICA Y UNA PROPUESTA OPERATIVA. - Castillo García, Rodolfo Francisco (2010)
The present article is a conceptual approximation to the concept of Urban Sustainable Development and an operative interpretation of his components for his specific application to the Peruvian reality. Likewise, this article practice a conceptual approximation to the Planning of the Urban Sustainable Development as emergent and integrator approach of modern urban planning; and propose some actions for his normative assimilation in Peru and for his operative application in the urban plans.